2011
DOI: 10.4103/2231-4040.85538
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antioxidant activity of green tea with some herbs

Abstract: Cardiovascular diseases, cancer, arthritis, etc. are caused by free radicals that are byproducts of metabolic pathways. Selected plants namely Vitis vinifera, Phyllanthus emblica L., Punica granatum, Cinnamomum cassia, Ginkgo biloba L., and Camellia sinensis Linn. are reported to produce antioxidant property. This study is undertaken to support the hypothesis that formulation of a polyherbal combination of these plants shows a synergistic effect with green tea. The extracts of each drug were characterized by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 25 publications
2
60
0
Order By: Relevance
“…Polyphenol compounds in the Phyllanthus plant play a major role in chemoprevention, inhibition of the invasion, migration and adhesion of cancer cells, along with the involvement in apoptosis induction (Lee et al, 2011). PE can be used either alone or in combination with other plants (Baliga, 2010;Jain et al, 2011), as it shows synergistic growth inhibitory effects with conventional cytotoxic agents, doxorubicin and cisplatin (Pinmai et al, 2008). This is another interesting point where even the mechanism remains unclear.…”
Section: Suppression Of Human Fibrosarcoma Cell Metastasis By Phyllanmentioning
confidence: 99%
“…Polyphenol compounds in the Phyllanthus plant play a major role in chemoprevention, inhibition of the invasion, migration and adhesion of cancer cells, along with the involvement in apoptosis induction (Lee et al, 2011). PE can be used either alone or in combination with other plants (Baliga, 2010;Jain et al, 2011), as it shows synergistic growth inhibitory effects with conventional cytotoxic agents, doxorubicin and cisplatin (Pinmai et al, 2008). This is another interesting point where even the mechanism remains unclear.…”
Section: Suppression Of Human Fibrosarcoma Cell Metastasis By Phyllanmentioning
confidence: 99%
“…To evaluate the antioxidant activity or super oxide radical scavenging activity of the steviol glycosides present in the extract of stevia following assays were studied 1) free radical scavenging capacity assay by DPPH (1,1-Diphenyl-2-picrylhydrazyl) method; 2) hydroxyl superoxide radical and 3) nitric oxide radical assay were carried out using standard methods [42]. The results obtained were compared with that of known anti-oxidants samples like green tea and ascorbic acid.…”
Section: Determination Of Antioxidant Activity Differentmentioning
confidence: 99%
“…Also, possible interactions for combined extracts of these natural antioxidants that show the ability of using very low doses of each individual extract in preventing oxidation in food systems which is the main purpose of present study has still not been evaluated even though some other studies has evaluated interactions between some antioxidants compounds (Romano et al 2009;Hidalgo et al 2010;Jain et al 2011;Li et al 2011;Yin et al 2012;Chanda et al 2013). The aim of the present study was to evaluate antioxidant properties of green tea, rosemary and oak fruit extracts individually and in combination and try to find specific combinations with least concentrations that exhibit synergistic effect which may help to use natural and safe antioxidants in very low doses instead of synthetic antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…These effects are not definite properties for plant extracts and drugs, but they are widespread properties related to the way they are explained and their ratios (Borgert et al 2005). Jain et al (2011) showed that a synergistic effect would enhance the antioxidant activity and thus make it possible to use lower doses of each extract and prevent the side effects of using large amounts of individual plant extracts.…”
Section: Introductionmentioning
confidence: 99%